Kaznivo dejanje zlorabe položaja v enoosebni družbi z omejeno odgovornostjo - Detiček Sgueglia, Antonella (Podjetje in delo, 2021)
Due to the absence of other partners, a single-person limited liability company constitutes a threatening legal institute, especially in terms of the matter of criminal liability for the criminal act of abuse of position or confidence in economic activity. Current judicial practice that allows punishing the director of the company, which is simultaneously the owner of the single-person limited liability company for the criminal act of abuse of position or confidence in economic activity, is problematic. Owing to the company structure, the agreement to damage of the company's property is always given, which raises the question of illegality of the criminal act. Parenting concept and the concept of separation of company's property from part-ner's property in single-person company for the purposes of criminal law are not appropriate, because the sole partner shapes the legal destiny of such a company. The need to enforce the principle of separation of company's property from the partner's property is reflected in the function of protecting the creditors or other beneficiaries of company's property. In this type of companies, the sole partner is represented as the "master" of the company, since he independently decides of its legal fate. It is absurd to claim that the legal person was harmed by its sole partner - the "master". As a result of the absence of internal relations between partners, the ownership and management function are united in one single person; therefore, the damage to one's own company is fictitious. By harming a single-person company, the individual is in fact damaging their own property, which they have legally converted to an independent legal person, but can be converted back into their own property by liquidating their own company.
Keywords: abuse of position; criminal liability; criminal liability of legal persons; criminal offense; enoosebna družba z omejeno odgovornostjo; kazenska odgovornost; kazenska odgovornost pravnih oseb; kaznivo dejanje; one-person limited liability company; zloraba položaja